Checkpoint Inhibitor Colitis Shows Drug-Specific Differences in Immune Cell Reaction That Overlap With Inflammatory Bowel Disease and Predict Response to Colitis Therapy. Issue 2 (8th February 2021) - Lo, Ying-Chun; Price, Christina; Blenman, Kim; Patil, Pallavi; Zhang, Xuchen; Robert, Marie E
Abstract: Objectives: Checkpoint inhibitor (CPI)–associated colitis can limit therapy and has resemblance to inflammatory bowel disease (IBD). Studies exploring mechanistic similarities between these colitides are limited, yet therapeutic targets for either disorder could emerge from shared pathophysiology. Methods: The morphology and inflammatory content of colonic biopsy specimens from anti–CTLA-4 and anti–PD-1/PD-L1 antibody-treated patients with CPI colitis were compared with initial biopsy specimens from patients with IBD. Predictors of the need for infliximab were sought in CPI patients. Results: Biopsy specimens from CPI patients showed significantly lower chronicity scores and similar activity scores compared with patients with IBD. Anti–CTLA-4 and IBD groups showed equivalent CD8, CD4, PD-1, and PD-L1 expression, while FoxP3 scores were lower and CD68 scores were higher in anti–CTLA-4 compared with IBD biopsy specimens. Anti–PD-1/PD-L1 group had lower scores for CD8, CD4, and PD-1 and equivalent scores for FoxP3, PD-L1, and CD68 compared with IBD. Anti–CTLA-4 biopsy specimens had higher scores for CD8, PD-1, PD-L1, and CD68 than anti–PD-1/PD-L1 biopsy specimens. CD8/FoxP3 ratios and CD68 scores were higher among CPI patients requiring infliximab therapy for colitis compared with those responding to steroids. Conclusions: The proinflammatory immune phenotype of anti–CTLA-4–associated colitis has significant overlap with IBD. CD8/FoxP3 ratios may predict therapeutic response in CPI-associated colitis.